LAND WETTING USING THE HYDRAM PUMP METHOD IN PREVENTING PEATLAND FIRES - Topan Eka Putra; Lola Cassiophea; Samuel Layang; Wiratno Y Sigin; Tuah; Danar Airangga Windra Gautama; Revianti Coenraad; Frans Putra Ganesa; Berkat Yuda (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
Peatlands are an ecosystem that has an important role in the environment, including carbon storage, biodiversity habitat, and water availability (Murdiyarso et al., 2010). However, peatlands are also very vulnerable to fire, especially in extreme dry season conditions (Page et al., 2002). Peatland fires can cause significant environmental losses, including greenhouse gas emissions, loss of biodiversity, and negative impacts on public health due to the smoke produced (Masykur et al., 2019). Therefore, efforts to prevent peatland fires are very important to maintain the sustainability of this ecosystem and public health. The hydram pump method was chosen as an innovative solution in this research because of its ability to pump water continuously without requiring an electricity or fuel source. This makes it a sustainable and environmentally friendly alternative for wetting peatlands, which in turn can increase soil moisture and reduce the risk of fire (Wardhana et al., 2021). By utilizing this method, it is hoped that soil moisture can be maintained, making the land less susceptible to fire. The type of research used is experimental research. The research location was carried out at the Building Engineering Education Laboratory, FKIP UPR with a hydram pump and a drip irrigation system on differences in land elevation from plant water sources and water use efficiency. The target achieved is that this research will be published in the SINTA 5 and HKI Accredited Journals.